Mixed Reality–Based Solar System Learning Media for Enhancing Technological Literacy and Student Interaction in Elementary Education - Galih Ashari; Eka Noviana; Sri Retnoningsih; Maulana Seno Aji; Muhammad Figo Razzan; Dhimas Aji; Muhammad Alif Syaikhan; Raka Gaizka A; Ariq Zaki Muhammad (Universitas Ahmad Dahlan, 2026)
Background: The rapid advancement of digital technology has encouraged the development of learning approaches that support not only knowledge acquisition but also collaboration and interaction. Contribution: This study proposes a Mixed Reality (MR)-based solar system learning media with multiplayer features to enhance technological literacy and student interaction in elementary education. Methods: An evaluative mixed-method approach was employed involving 37 students and 8 teachers at SDIT Daarul Jihad. Data were collected through questionnaires, observations, and interviews, and analyzed using descriptive statistics and qualitative interpretation. Results: The findings show that the MR-based learning media was positively perceived by both teachers and students. More than 88% of teachers reported improved student understanding and engagement, while over 90% of students experienced increased motivation and ease of use. In addition, 76.9% of students demonstrated high to very high confidence in explaining solar system concepts. The multiplayer feature also supported collaborative interaction and active discussion during learning activities. Conclusions: The MR-based collaborative learning media demonstrates strong potential in enhancing both cognitive and social aspects of learning in elementary education and provides practical insights into the integration of immersive collaborative learning technologies in classroom settings.